Nonradiative energy transfer between doped and undoped flat semiconductor nanocrystals of colloidal quasi-2D nanoplatelets - Yeltik, Aydan (2020)
Atomically flat colloidal semiconductors such as nanoplatelets (NPLs) promise great potential for different optoelectronic applications. Here, we systematically investigate the excitonic energy transfer from colloidal Cu-doped CdSe to undoped core/shell CdSe/CdS nanoplatelets via steady-state and time-resolved photoluminescence spectroscopy techniques. We show the strong quenching in photoluminescence emission of the doped NPL donors together with significant modifications in the time-resolved kinetics by changing the concentration of the undoped NPL acceptors in close proximity. This newly presented all-colloidal and all-quasi-2D doped–undoped NPL–NPL hybrid system shows near-unity room-temperature energy transfer efficiency (99%) in solid films. We strongly believe that such highly efficient energy transfer in doped–undoped hybrid films will create more interest in the scientific community to further explore different donor/acceptor combinations with these newly reported doped NPLs for next-generation energy harvesting applications.